Diatoms from the bottom sediments of Lake Shira (Khakassia, Russia) - Valieva, Elvira A; Nigmatullin, Niyaz M; Nigamatzyanova, Gulnara R; Frolova, Anastasia A; Nurgaliev, Danis K; Frolova, Larisa A (PANGAEA, 2023)
Diatoms are good indicators of a variety of lake water conditions including salinity, pH, light availability, temperature and nutrient levels, but diatoms as palaeoindicators are poorly studied in the Lake Shira. Our research on the species composition and ecological parameters of diatoms provide additional data for the regional databases and contributes to improving the accuracy of paleoecological reconstructions. In this study the diatom results of analysis a 528 cm long continuous sediments core from the Lake Shira (Khakassia, Russia) are presented. The core was collected in August 2020 from central part of the lake from a depth of 24 m. 39 samples were investigated by us for diatom analysis. Diatoms were found only in 13 samples. Diatom analysis of samples revealed 30 taxa, belonging to 19 genera. The analysis of the ecological structure of the diatom flora of the sediment core sample from the lake under study shows that it is dominated by the cosmopolitan representatives of benthic and planktonic-benthic, indifferent to salinity and halophiles organisms giving preference to the alkaline environmental conditions. The prevalence of Handmannia comta (Ehrenberg) Kociolek & Khursevich diatom in sediments have been established.